The Role of NRF2 in Mycobacterial Infection - Masashi Matsuyama; Mizu Nonaka; Masayuki Nakajima; Yuko Morishima; Yukio Ishii; Nobuyuki Hizawa (MDPI AG, 2021)
The incidence of pulmonary nontuberculous mycobacterial (NTM) infection is increasing worldwide, and its clinical outcomes with current chemotherapies are unsatisfactory. The incidence of tuberculosis (TB) is still high in Africa, and the existence of drug-resistant tuberculosis is also an important issue for treatment. To discover and develop new efficacious anti-mycobacterial treatments, it is important to understand the host-defense mechanisms against mycobacterial infection. Nuclear erythroid 2 p45-related factor-2 (NRF2) is known to be a major regulator of various antioxidant response element (ARE)-driven cytoprotective gene expressions, and its protective role has been demonstrated in infections. However, there are not many papers or reviews regarding the role of NRF2 in mycobacterial infectious disease. Therefore, this review focuses on the role of NRF2 in the pathogenesis of Mycobacterium tuberculosis and Mycobacterium avium infection.